LINGUISTIC FEATURES OF COMPUTER TERMINOLOGY IN ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2023)
The article describes the linguistic research of computer and internet terms that are common in the current globalisation process. One of the peculiarities of computer and internet terminology is that they can be understood and used even among the general public. From this point of view, we have found that computer terminology, the etymology of computer terminology, the metaphorical characteristics should bring different aspects of its acceptance by terminologists and lexicographers. In the course of this study, the process of mastering English terms in the terminology of the Uzbek language, their origin were analyzed.